Do investments in human capital lead to employee share ownership? Evidence from French establishments. (August 2016) - Guery, Loris; Pendleton, Andrew
Investments in human capital can create a hold-up problem whereby both employers and employees exploit the bargaining weaknesses of the other. Employee share ownership (ESO) can mitigate this hold-up problem because it can align interests, develop loyalty, signal good-will and lock in employees. Previous studies have shown positive relationships between company investments in human capital and the use of ESO consistent with this argument but have been unable to identify the direction of causality. Using panel data from the French REPONSE survey, the findings indicate that significant and continuous investments in human capital take place prior to the implementation of ESO.